Experimental Analysis of Light Weight Concrete Using EPS Balls and Steel Fibres - Suraj Memane; Saurabh Chaudhari; Abhijeet Darekar; Omkar Tupe; Prabhakar Waingade; Prof. Omkar Gangatire (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Waste EPS is an environmental hazard. It is a non-biodegradable material, if not controlled can cause depletion of ecosystem. It can also be reused in construction industry to produce light weight concrete with exceptionally low density. When coarse aggregate is replaced with EPS beads, we get a low density concrete. The density of the resultant concrete can be achieved so low that the formed concrete might just float, with its density being less than that of water’s. Light weight concrete show a decrease in the durability behavior and engineering properties with introduction of more polystyrene aggregate. Along with EPS beads, fibres and super-plasticizers are to be used to overcome the brittle failure of EPS. A comparative study of mechanical properties of conventional concrete, conventional concrete along with EPS beads and Conventional concrete with EPS beads and fibres is to be studied. M20 grade of concrete is used with partial replacement of coarse aggregate with 40%, 50%, 60% EPS beads containing steel and glass fibres. The goal of this project is to replace coarse aggregate with EPS and artificial fibres, resulting into light weight concrete. Super-plasticizer (aura mix-400) is used to enhance the workability of concrete. Artificial fibres contribute to increase the compressive strength of light weight concrete. The content of steel and glass fibres used is 1% and 0.25% by weight of cement respectively. The motive of this experimental investigation is to enhance the compressive strength of EPS concrete by inducing artificial fibres.
Keywords: EPS (expanded polystyrene beads); conventional concrete; super plasticizer (aura mix-400); artificial fibres; double hooked steel fibres; glass fibres